SVep1, a temperate phage of human oral commensal Streptococcus vestibularis - Wu, Miaomiao; Zhu, Yanpeng; Yang, Yuhui; Gong, Yali; Chen, Zongyue; Liao, Binyou; Xiong, Yu; Zhou, Xia; Li, Yan (Frontiers in Microbiology, 2023)
Introduction Bacteriophages play a vital role in the human oral microbiome, yet their precise impact on bacterial physiology and microbial communities remains relatively understudied due to the limited isolation and characterization of oral phages. To address this gap, the current study aimed to isolate and characterize novel oral phages. Methods To achieve this, oral bacteria were isolated using a culture-omics method from 30 samples collected from healthy individuals. These bacteria were then cultured in three different types of media under both aerobic and anaerobic conditions. The samples were subsequently subjected to full-length 16S rRNA gene sequencing for analysis. Subsequently, we performed the isolation of lytic and lysogenic phages targeting all these bacteria. Results In the initial step, a total of 75 bacterial strains were successfully isolated, representing 30 species and 9 genera. Among these strains, Streptococcus was found to have the highest number of species. Using a full-length 16S rRNA gene similarity threshold of 98.65%, 14 potential novel bacterial species were identified. In the subsequent phase, a temperate phage, which specifically targets the human oral commensal bacterium S. vestibularis strain SVE8, was isolated. The genome of S. vestibularis SVE8 consists of a 1.96-megabase chromosome, along with a 43,492-base pair prophage designated as SVep1. Annotation of SVep1 revealed the presence of 62 open reading frames (ORFs), with the majority of them associated with phage functions. However, it is worth noting that no plaque formation was observed in S. vestibularis SVE8 following lytic induction using mitomycin C. Phage particles were successfully isolated from the supernatant of mitomycin C-treated cultures of S. vestibularis SVE8, and examination using transmission electron microscopy confirmed that SVep1 is a siphovirus. Notably, phylogenetic analysis suggested a common ancestral origin between phage SVep1 and the cos-type phages found in S. thermophilus. Discussion The presence of SVep1 may confer immunity to S. vestibularis against infection by related phages and holds potential for being engineered as a genetic tool to regulate oral microbiome homeostasis and oral diseases.